If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 5 + -3x Solving 21 = 5 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 21 + 3x = 5 + -3x + 3x Combine like terms: -3x + 3x = 0 21 + 3x = 5 + 0 21 + 3x = 5 Add '-21' to each side of the equation. 21 + -21 + 3x = 5 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 5 + -21 3x = 5 + -21 Combine like terms: 5 + -21 = -16 3x = -16 Divide each side by '3'. x = -5.333333333 Simplifying x = -5.333333333
| x^2+4x-47=0 | | -4x+12=-4(2x+4) | | -22x+6=-14x+70 | | (5x-21)+56=180 | | n/2-410= | | x^2-31x+228=0 | | 9x-(5x-10)=42 | | -14x^2-9x-10=0 | | 5x-3=-3x+35 | | 13=8-x+x | | 2x^3/3y^3/2x/y | | 23x-8=128 | | 5x+4=-14y | | y=2.7x-3.6 | | 15x=33 | | 2x+3y(x)+8=36 | | 0=-16t^2+128t+90 | | 0=-16t^2+128+90 | | -4(5n+5)+4n= | | X^2+630x-3125=0 | | 22m=6 | | 16y=20-2x | | e^6x-2e^3x-3x=0 | | y+218=6y+8 | | 5x+18=96 | | b+315=-6b+7 | | (5x+6)+(3x+23)=(9x+12) | | 180-x-(x+10)-(3x-5)=0 | | (x(X-9)(5x-18)^2)/3 | | X-5+10=25 | | 9x+36-34= | | (A^4/b^2c)^5 |